PERBEDAAN PENGARUH SENAM HAMIL DAN EDUKASI TERHADAP PENINGKATAN KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III - Sari Fauziyah Maharani; Dwi Kurniawati; Marti Rustanti (Jurnal Nasional Fisioterapi, 2023)
Background: A significant increase in fetal weight and length will occur in the third trimester of pregnancy, it can cause discomfort felt by pregnant women in the pelvic and abdominal area. The appearance of regular contractions also causes pain in pregnant women. Third trimester pregnancy will occur emotional instability in pregnant women, namely the feeling of pleasure welcoming the presence of a baby, but sometimes it also causes anxiety in pregnant women. These things can reduce sleep quality in pregnant women. Objective: to determine the different effect of pregnancy exercise and education on improving the quality of sleep of pregnant women in the third trimester. Method: This study uses quasi experiment two group pre and post test research method design. The subjects consisted of 30 people divided into two groups. Group I was given pregnancy exercise treatment and group 2 received education. Sleep quality measurements were taken before and after treatment using PSQI. Result: Pre-post test difference test using Wilcoxon test in group I & II, in Group I obtained result p = 0.001, and in group II obtained a result of p = 0.001. The difference between group I and II post tests using the Mann-Whitney test obtained p = 0.373 results. Conclusion: there was no significant difference in sleep quality of pregnant women between the two groups.